2011
DOI: 10.1007/978-3-642-22362-4_35
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Socioeconomic Levels Using Cell Phone Records

Abstract: Abstract. The socioeconomic status of a population or an individual provides an understanding of its access to housing, education, health or basic services like water and electricity. In itself, it is also an indirect indicator of the purchasing power and as such a key element when personalizing the interaction with a customer, especially for marketing campaigns or offers of new products. In this paper we study if the information derived from the aggregated use of cell phone records can be used to identify the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
100
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(103 citation statements)
references
References 13 publications
2
100
0
1
Order By: Relevance
“…Previous research using cell phone calling logs has already shown that cell phone-based behavioral patterns are correlated to specific socio-economic characteristics [3,11]. For example, Eagle et al showed correlations between the size of a cell phone social network and the socioeconomic level of a person, and Frias et al observed strong relationships between mobility and socio-economic indices [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research using cell phone calling logs has already shown that cell phone-based behavioral patterns are correlated to specific socio-economic characteristics [3,11]. For example, Eagle et al showed correlations between the size of a cell phone social network and the socioeconomic level of a person, and Frias et al observed strong relationships between mobility and socio-economic indices [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Eagle et al showed correlations between the size of a cell phone social network and the socioeconomic level of a person, and Frias et al observed strong relationships between mobility and socio-economic indices [6]. Additionally, Soto et al showed that the socioeconomic level(SEL) of a region at a given moment in time, can be predicted from cell phone activity during the same time period with an 80% of accuracy using training sets containing both SELs and calling activity [11,4]. Although this work threw some light onto the predictability of SELs using calling data, it focused on predicting the present i.e., SEL values at a specific moment in time rather than forecasting future values.…”
Section: Introductionmentioning
confidence: 99%
“…We have empirically evaluated CenCell with millions of cell phone records from urban citizens and we have shown that it correctly determines the socioeconomic levels computed by the NSIs with high accuracies (Soto et al 2011). Thus, CenCell significantly decreases the workload of the enumerators that carry out the interviews and as such, allows us to reduce the budget allocated for the computation of census maps.…”
Section: Social Economics and Policymentioning
confidence: 99%
“…Using information from mobile phone call records through a plurality of base stations, it has been shown how the prediction of socioeconomic level in a geographic region can automatically be performed [24,25]. Prediction accuracy depends on the kind of variable (for example, predicting gender from mobile phone behavior is surprisingly tricky [26,27]), but generally it has been shown to be around 80-85% when using mobile call data records like call duration or frequency [24,[26][27][28]. Such ideas can be fine-tuned for cases where more detailed digital footprints are available.…”
Section: Big Data and Developmentmentioning
confidence: 99%